Oral translation as a way of fostering accuracy. Evidence from teaching Russian - Laskova, Vesselina (Studia Rossica Posnaniensia, 2022)
This paper presents the results from two different experiments carried out independently with two different groups of students using the same materials and the same methodology, with the aim to check whether oral translation, if applied as a main teaching technique, can foster the development of the accuracy component of language proficiency. The experiments were carried out at the International Centre for Plurilingualism at the University of Udine with two experimental groups over a period of three years. Apart from providing a positive answer to the research question, the results show that the whole training can be carried out as part of the in-class activities and is independent of factors of personal character like the amount of time a student dedicates to the L2 learning at home, his or her willingness to put him/herself to work and even, to a large extent, independent of the student’s mother tongue or previous contacts with the foreign language. Since the main goal is the rapid memorization of the lexical and grammar material inside a context, the present technique suggests itself as a promising teaching tool in any lexically specialized field of L2 study.